2023
DOI: 10.1002/alz.13157
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal changes in Alzheimer's‐related plasma biomarkers and brain amyloid

Abstract: INTRODUCTIONUnderstanding longitudinal plasma biomarker trajectories relative to brain amyloid changes can help devise Alzheimer's progression assessment strategies.METHODSWe examined the temporal order of changes in plasma amyloid‐β ratio (), glial fibrillary acidic protein (GFAP), neurofilament light chain (NfL), and phosphorylated tau ratios (, ) relative to 11C‐Pittsburgh compound B (PiB) positron emission tomography (PET) cortical amyloid burden (PiB−/+). Participants (n = 199) were cognitively normal at … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 57 publications
1
14
0
Order By: Relevance
“…Although the general patterns of protein-based risk factor associations with plasma and cortical Aβ were similar, the sample size for cortical Aβ was smaller, with considerably less statistical power to detect effects. Although prior studies suggest that plasma Aβ 42/40 is predictive of cortical Aβ PET positivity, 47 several studies-including one from our group 48 -show that plasma Aβ 42/40 declines prior to and is predictive of elevations in cortical Aβ (measured using PET). 49 Thus, given the cognitively normal sample, Aβ 42/40 may provide a more meaningful indicator of Aβ burden, particularly among this sample, where 71% of participants do not have elevations in cortical amyloid.…”
Section: Discussionmentioning
confidence: 71%
“…Although the general patterns of protein-based risk factor associations with plasma and cortical Aβ were similar, the sample size for cortical Aβ was smaller, with considerably less statistical power to detect effects. Although prior studies suggest that plasma Aβ 42/40 is predictive of cortical Aβ PET positivity, 47 several studies-including one from our group 48 -show that plasma Aβ 42/40 declines prior to and is predictive of elevations in cortical Aβ (measured using PET). 49 Thus, given the cognitively normal sample, Aβ 42/40 may provide a more meaningful indicator of Aβ burden, particularly among this sample, where 71% of participants do not have elevations in cortical amyloid.…”
Section: Discussionmentioning
confidence: 71%
“…The assumption of a hypothetical common curve is an extension of prior work described by Jack et al 21,22 and has been similarly implemented in other recently described temporal modeling approaches. 20,23,25,27 In this study, we extended prior AFT models to accommodate five biomarker outcomes: Aβ PET meta-ROI, tau PET temporal meta-ROI, plasma p-tau217, plasma p-tau181, and GFAP. Aβ and tau PET were natural log-transformed to account for skewness.…”
Section: Primary Model and Individual Adjustmentsmentioning
confidence: 99%
“…16,17 Limited longitudinal modeling studies suggest that plasma p-tau181 and p-tau217 become abnormal around the same time or within several years after Aβ PET and precede changes in tau PET. [18][19][20] While these studies provide information on the timing of change in the population, they do not explain how plasma p-tau and PET biomarker changes are related on the individual level. Both are of interest.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies found plasma p-tau217 and p-tau181 were associated with amyloid PET, 16,36,[41][42][43][44] and could distinguish Aβ+ from Aβ-, 11,14,16,23,36,[45][46][47][48] which implied that plasma p-tau reflected the brain amyloid pathology. Comparing to plasma p-tau181, p-tau217 could more accurately distinguish Aβ+ from Aβ-in community residents in the MCSA.…”
Section: Supporting Informationmentioning
confidence: 99%